PENGARUH PERENCANAAN PAJAK, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP PRAKTEK MANAJEMEN LABA - Wira Santana, Dewa Ketut; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
Earnings management is the management condition to intervene in the process of preparation of financial statements for external parties can sehngga leveling , raising and lowering profits . This study aims to determine the effect of tax planning , the size of the company and managerial ownership on earnings management practices . The population in this study consisted of 159 companies listed on the stock exchange Indonesia with the observation period starting from 2008 to 2010 . Sampling using purposive sampling . The number of companies that meet the criteria of the study sample were as many as 26 companies . Analysis technique used is the technique of multiple linear regression analysis. Tax planning Pengujan results showed a positive effect on earnings management practices , while the managerial ownership and the size of the company showed no effect results
Keywords: Earning Management; Tax Plan; Managerial Ownership; Size